2018
DOI: 10.1093/eurheartj/ehy806
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of obstructive coronary artery disease and prognosis in patients with suspected stable angina

Abstract: Aims We hypothesized that the modified Diamond–Forrester (D-F) prediction model overestimates probability of coronary artery disease (CAD). The aim of this study was to update the prediction model based on pre-test information and assess the model’s performance in predicting prognosis in an unselected, contemporary population suspected of angina. Methods and results We included 3903 consecutive patients free of CAD and heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
21

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(140 citation statements)
references
References 21 publications
1
103
0
21
Order By: Relevance
“…All recruiting centres in PROMISE were in North America. Reeh et al 4 retrospectively assessed 3903 patients who underwent invasive angiography at a single Danish centre for investigation of suspected angina. Most patients had already undergone at least one other test prior to angiography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All recruiting centres in PROMISE were in North America. Reeh et al 4 retrospectively assessed 3903 patients who underwent invasive angiography at a single Danish centre for investigation of suspected angina. Most patients had already undergone at least one other test prior to angiography.…”
Section: Discussionmentioning
confidence: 99%
“…The guideline has updated estimation of pre-test probability for obstructive coronary artery disease based on chest pain type, age, and gender using more contemporaneous data from the Coronary CT Angiography Evaluation For Clinical Outcomes: An International Multicenter (CONFIRM) Registry, the CT group of the Prospective Multicenter Imaging Study for Evaluation of Chest Pain (PROMISE) randomized controlled trial and a retrospective single-centre angiographic cohort. 1 , 3 , 4 , 6 The thresholds that warrant further downstream testing have also been revised such that patients with a pre-test probability <5% are not recommended to undergo further testing, while testing is deemed appropriate in those with a pre-test probability >15%. Patients with an intermediate pre-test probability of 5–15% are recognized to have a good prognosis and testing may safely be deferred, although discretionary investigation can have a role.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in concordance with the latest data from the European Heart Network which shows that systolic blood pressure and total cholesterol levels are the determinants with the greatest contribution to CVD mortality 17. Also, these two factors are included in the widely used SCORE charts (3), and there are many clinical models that add them for increasing the probability of obstructive CAD 36–39…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that an outcome in patients with the new PTP of up to 15% is good (annual risk of cardiovascular death or myocardial infarction [MI] <1%; [ 8 , 9 ]). Hence, it would be safe to defer routine testing in patients with PTP <15%, thus reducing unnecessary procedures.…”
Section: Ptp and Clinical Likelihood Of Cadmentioning
confidence: 99%